Association between obesity, cardiometabolic risk, and body composition in Gorontalo women - Nuryani; Khomsan Ali; Dewi Mira; Meti Dwiriani Cesilia; Lukito Widjaja; Reski Amalia Mutia; Zalbahar Nurzalinda (BIO Web of Conferences)
Cardiovascular diseases are current issues that increase morbidity. Risk factors for cardiometabolic diseases include hyperlipidaemia, obesity, elevated blood glucose and blood pressure. The aim of study to determine associations between cardiometabolic risks and body composition with obesity among adult women in Gorontalo district. A total of 223 women adults were recruited using simple random sampling at two health centres in the Gorontalo district. Data were collected between August and October 2023. Cardiometabolic risk factors were determined through the measurements of cholesterol levels, blood glucose and blood pressure while the body composition parameters included body water, muscle mass, visceral fat, bone mass and waist circumference. Study was conducted using questionnaires and direct measurements. Statistical analyses were performed using Pearson and Spearman correlations method. A total of 84.4% of the women having central obesity. A significant association was found between body mass index with fasting blood glucose, blood pressure, waist circumference, muscle mass, visceral fat, body water, body fat, and bone mass (p=0.000). Obesity aggravates the risk of cardiovascular disease, thus maintaining nutritional status through physically active and dietary management is essential to prevent cardiometabolic risk.